2012
DOI: 10.1111/j.1469-8137.2012.04299.x
|View full text |Cite
|
Sign up to set email alerts
|

Silicon nutrition increases grain yield, which, in turn, exerts a feed‐forward stimulation of photosynthetic rates via enhanced mesophyll conductance and alters primary metabolism in rice

Abstract: SummarySilicon (Si) is not considered to be an essential element for higher plants and is believed to have no effect on primary metabolism in unstressed plants. In rice (Oryza sativa), Si nutrition improves grain production; however, no attempt has been made to elucidate the physiological mechanisms underlying such responses.Here, we assessed crop yield and combined advanced gas exchange analysis with carbon isotope labelling and metabolic profiling to measure the effects of Si nutrition on rice photosynthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
161
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 260 publications
(181 citation statements)
references
References 52 publications
(92 reference statements)
15
161
4
1
Order By: Relevance
“…Keywords: silicon (Si), signaling, metabolite profile, amino acid remobilization between Si concentration and the levels of compounds intimately associated with respiration (isocitrate and 2-oxoglutarate), and a handful of amino acids (alanine, arginine, glutamine, ornithine, isoleucine, methionine and valine). 12 When taken together, we clearly demonstrated that, at least under the conditions explored in our study, Si nutrition plays an important role in modulating the rate of flux from 2-oxoglutarate into amino acid metabolism, supporting the emergent view that amino acid metabolism is a tightly and intricately controlled network. 13,14 Accordingly, an increased incorporation of amino acids in storage proteins could be anticipated.…”
Section: Metabolic Alterations Triggered By Silicon Nutritionsupporting
confidence: 73%
See 3 more Smart Citations
“…Keywords: silicon (Si), signaling, metabolite profile, amino acid remobilization between Si concentration and the levels of compounds intimately associated with respiration (isocitrate and 2-oxoglutarate), and a handful of amino acids (alanine, arginine, glutamine, ornithine, isoleucine, methionine and valine). 12 When taken together, we clearly demonstrated that, at least under the conditions explored in our study, Si nutrition plays an important role in modulating the rate of flux from 2-oxoglutarate into amino acid metabolism, supporting the emergent view that amino acid metabolism is a tightly and intricately controlled network. 13,14 Accordingly, an increased incorporation of amino acids in storage proteins could be anticipated.…”
Section: Metabolic Alterations Triggered By Silicon Nutritionsupporting
confidence: 73%
“…11 We have recently demonstrated that Si nutrition impacts the source-sink relationship and stimulates amino acid remobilization in rice. 12 We demonstrated that Si-treated plants have reduced levels of several amino acids, a fact linked with an augmentation of the sink strength which was clearly mediated by Si nutrition with little, if any, impact on growth per se. 12 Although Si did not affect the actual rate of 14 C incorporation into amino acids (Table 1), our data support a role for Si nutrition in orchestrating amino acid remobilization.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Silicon is attributed with many beneficial effects for the cultivation of rice, as it increases the tolerance of plants to the abiotic stress caused by drought and biotic stress and reduces the incidence of diseases such as Pyricularia (Mauad, Costa, Cruscial, Grassi-Filho and Corrêa, 2013), because this nutrient reinforces the cell wall (Epstein, 1999) and, thereby, increases the mass and grain production (Detmann et al, 2012), also it helps to maintain high amounts of dry biomass (Tamai and Ma, 2008).…”
Section: Introductionmentioning
confidence: 99%